Sufism : a global history - Green, Nile. (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
Since the emergence of Sufism in the ninth century, the shrines, brotherhoods and doctrines of the Sufis have held vast influence in almost every corner of the Muslim world. Offering the first truly global account of the history of Sufism, this illuminating book traces the gradual spread and influence of Sufi Islam through the Middle East, Asia, Africa, and ultimately into Europe and the United States. Moving beyond the description of doctrine, this book places Sufism in its social, cultural and historical contexts. It dismantles the stereotypes of Sufis as otherworldly "mystics" by anchoring Sufi Muslims in the lives of their communities. It explores Sufism's cross-cultural links with music, poetry, architecture and folk traditions, and delves into the social and political factors by which Sufi holy men gained followers among not only tribesmen and peasants but also emperors and bureaucrats--alliances that made leading Sufis powerful even at the height of European colonization. Requiring no background knowledge of Islamic history or doctrine, this book provides readers with an ideal introduction to Sufism as a global phenomenon. It explores not only the theology and ritual of Sufism but also its influence in shaping societies and cultures across the world.
Origins, foundations and rivalries (850-1100) -- An Islam of saints and brothers (1100-1400) -- Empires, frontiers and renewers (1400-1800) -- From colonization to globalization (1800-2000) -- Glossary: A Sufi lexicon of Arabic terms.
Includes bibliographical references and index.
Keywords: Geschichte; Sufism -- History; Sufismus